Vegetable oil-based, coumarin-containing antibacterial thermosets with improved thermal stability via copper-free thermal azide-alkyne click polymerization - ÇAKMAKÇI, EMRAH; ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2022)
In recent years, the preparation of thermoset materials based on renewable sources has received peculiar attention. In this work, we prepared vegetable oil based antibacterial thermosets via thermal azide-alkyne cycloaddition reactions. Dimer diamine was propargylated and mixed with azidated trimethylolpropane triglycidyl ether and castor oil bearing azide and phosphorous groups. Two different propargyl functionalized marins were also incorporated into the vegetable oil based formulations. All synthesized monomers characterized by Fourier-transform infrared (FTIR) and Nuclear magnetic resonance (NMR) spectroscopy. chanical, thermal and antibacterial properties of the obtained thermosets were also determined. The thermosets behaved as elastomers and displayed elongation at break values between 39% and 82%. The phosphorylated castor oil derivative improved the thermal properties and char yields as high as 13.83% at 750 ? were observed under nitrogen atmosphere. Coumarin-containing thermosets were found to have antibacterial activity against both gram-positive and gram-negative bacteria.
Keywords: Tarımsal Bilimler; Ziraat; Toprak ve Bitki Besleme; Toprak Verimliliği ve Gübreleme; Agricultural Sciences; Agriculture; Soil and Plant Feed; Soil Fertility, Acidity, Alkanility; ZİRAAT MÜHENDİSLİĞİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); TARIM BİLİMİ; AGRICULTURAL ENGINEERING; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); AGRONOMY; Agronomi ve Mahsul Bilimi; Genel Tarım ve Biyoloji Bilimleri; Yaşam Bilimleri; Agronomy and Crop Science; General Agricultural and Biological Sciences; Life Sciences; Castor oil; Dimer diamine; Azide-alkyne click reaction; Phosphorus; Coumarin; Antibacterial; EPOXY THERMOSETS; FLAME-RETARDANT; SOYBEAN OIL; CASTOR-OIL; CHEMISTRY; DERIVATIVES; ISOSORBIDE; POLYMERS; COATINGS; RESINS; Castor oil; Dimer diamine; Azide-alkyne click reaction; Phosphorus; Coumarin; Antibacterial